PERBEDAAN PENGUKURAN OBJEKTIF AKTIVITAS FISIK DENGAN FUNGSI KOGNITIF PADA ANAK USIA 4 TAHUN - Tedi Apriansyah, - (2020)
Early childhood is a period of rapid physical and cognitive development, at which time a child's habits begin to form. Lifestyle behaviors that are developed early in life can affect the level and pattern of physical activity in his life. Having an active role in aktivitas fisik can benefit the process of developing motor skills and cognitive development. Growth and physical development and cognitive of children is one thing that is very important to note. However, there are still many children who do not do physical activity in accordance with the recommendations and guidelines that have been agreed to know the time spent by children in doing physical activity every day, and the benefits of physical activity on cognitive function. Therefore, the aim of this study is to examine differences in objective measurement of physical activity and cognitive function in children aged 4 years. The method used in this study is causal comparative with the population in this study are children aged 4 years who are attending kindergarten, PAUD, and Study Groups in Bandung City and West Bandung Regency. Involved 40 children aged 4 years who participated as a sample in this study. Data collection with an objective method is done using the ActiGraph accelerometer to measure physical activity and EYT Toolbox Go No Go and EYT Toolbox Mr. Ant to measure cognitive function in children aged 4 years. The result, the difference in objective measurement of a physical activity in 4-year-olds is p (0.00) <0.05, which means there is a significant difference, while differences in objective measurement of fungsi kognitif in 4-year-olds are obtained p (0.297) > 0.05, which means there is no significant difference. Keywords: Objectively Measured, Physical Activity, Cognitive Function, Children 4 years of age.